Functionalization of Nanosystems in Cancer Treatment - Luiz, Marcela Tavares (2022)
Cancer is the major public health problem worldwide, with high rates of incidence and lethality. The leak of specificity of the treatments currently available results in several side effects and reduced efficacy. Thus, nanosystems have demonstrated great potential for the delivery of chemotherapeutic agents to tumors due to their ability to passively accumulate in the tumor through enhanced permeability and retention (EPR) effect, to carry of hydrophilic and hydrophobic drugs, and to protect the drugs against degradation. In recent decades, advances in nanosystems design have expanded their therapeutic potential due to the inclusion of targeting ligands that can be specifically recognized by receptors overexpressed on tumor cells. Among these targeting ligands, antibodies, antibodies’ fragments, peptides, and small molecules have been widely incorporated in nanosystems for promoting the active targeting to the tumors. The modification of nanosystems with these ligands can be performed before or after nanosystems’ production through non-covalent or covalent functionalization, which can result in different biological activities. In this context, the present chapter aims to present some aspects of the synthesis employed to functionalize nanosystems. In addition, we address the main targeting ligands used for promoting the active targeting of nanosystems to different cancer cells, discussing the in vitro and in vivo results obtained for each functionalization.